Multi - Criterion Decision Making Approach to Assess Retail Service Quality : A Market Perspective from Iraq - Rashid, Abdul; Rokade, Varsha (Prabandhan: Indian Journal of Management, 2021)
The objective of this research was to analyze the relative importance of different retail service quality (RSQ) criteria on customer satisfaction (CS) through multi-criterion decision making approach (Analytic Hierarchy Process). The organized retail food and grocery outlets were selected from four major cities of Iraq, that is, Baghdad, Basrah, Al Mawsil al Jadidah, and Erbil. Data were gathered from 13 experts in organized retail via specially designed AHP questionnaire and analyzed through pairwise comparison by AHP. Weights for RSQ criteria, that is, Physical Aspects, Convenience, Reliability, Problem Solving, Personal Interaction, and Technological Advancement were calculated. Internal pairwise comparison among different criteria and sub - criteria of RSQ was done. To reveal the relative importance of each criteria and sub-criteria of RSQ, the hierarchical framework was drawn. It was found that Technological Advancement of RSQ had maximum weightage on building CS ; whereas, Personal Interaction had minimum weightage. In sub-criteria comparison, ‘mobile application for placing the order’ had maximum weightage on CS, while ‘no customers waiting because of retailer gossiping’ had minimum weightage. It was concluded that a web based mobile application for online shopping and placing orders was an important parameter in building CS in organized retail food and grocery customers in the afore - mentioned cities of Iraq.